Thermosensitive transfer printing ink as well as preparation method and application thereof
By using modified ferrotetraoxide composite materials and carboxylated kaolin in thermal transfer inks, combined with silicone-containing phenolic resin, to form an interpenetrating network structure, the coloring power, adhesion fastness and The problem of insufficient initial dryness has achieved higher ink performance and a wider range of applications.
Patent Information
- Application Number
- CN202411787195.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-12-05
AI Technical Summary
The coloring power and adhesion fastness of existing thermal transfer inks are relatively low, and the initial dryness needs to be improved, resulting in limited application.
By using modified ferrooxide composites and carboxylated kaolin, and other components, the introduction of silicon-containing phenolic resins into the polymer system, forming an interpenetrating network structure to improve the adhesion fastness and coloring power of the ink, and carboxylation by carboxylation Kaolin optimizes the volatility rate of solvents and improves primary dryness.
It significantly improves the coloring power, adhesion fastness and initial dryness of the thermal transfer ink, enhances the printing suitability and stability of the ink, and expands its application range.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of inks, and in particular relates to a thermal transfer ink and a preparation method and application thereof. Background Art
[0002] Thermal transfer technology is a special technology based on hot melt technology. Its basic principle is that the resin particles in the thermal transfer ink undergo a thermal melt effect under the action of heat conduction and pressure from a semiconductor electric heating head or laser, thereby transferring the graphic information to the surface of the printing material to form images and text. Thermal transfer ink is the most critical material in thermal transfer imaging technology. Thermal transfer ink is applied to the base material in the form of a coating. When not subjected to heat, the thermal transfer ink is stably fixed on the base material without any sticking or dirtying. When the base material is subjected to heat from an electric heating head or laser, the pigment microcapsule particles in the thermal transfer ink are immediately transferred to the printing material along with the thermal melt process, forming a trace of graphic information.
[0003] A Chinese patent (publication number CN117924995A) discloses a thermal transfer ink and its preparation method and application. It utilizes the excellent solvent release and printing adaptability of polymers, and is matched with different proportions of ester cellulose or ether cellulose and chloroacetate resins. The three types of components cooperate with each other to achieve the printing adaptability, solvent release and post-processing performance of thermal transfer inks containing benzene and ketones when there is no benzene or ketone. The benzene-free and ketone-free ink in this invention can retain good fineness, viscosity, and low solvent residue, and does not contain harmful ketone and benzene solvents, which is more environmentally friendly and safe. However, this patent does not solve the problem that the coloring power and adhesion fastness of thermal transfer inks in the prior art are both low, and the initial drying property needs to be improved, which limits its application.
[0004] Therefore, there is an urgent need for a thermal transfer ink that can effectively improve the coloring power and adhesion fastness of the ink and ensure good initial drying properties by modifying the pigment components and combining them with suitable polymer materials. Summary of the invention
[0005] The purpose of the present invention is to provide a thermal transfer ink and a preparation method and application thereof, by using a modified ferrosoferric oxide composite material and carboxylated kaolin, and matching other components to obtain a mixed filler, and at the same time introducing a silicon-containing phenolic resin into the polymer system, the tinting power and adhesion fastness of the ink are effectively improved, and good initial drying properties are ensured.
[0006] In order to achieve the above object, the present invention provides the following technical solutions: The first aspect of the present invention provides a method for preparing a thermal transfer ink, comprising the following steps: Step S1: in parts by weight, 120-140 parts of anhydrous ethanol and 30-40 parts of deionized water are mixed evenly, and then 1-3 parts of ferroferric oxide are added for ultrasonic dispersion for 40-60 minutes, and then 8-10 parts of tetraethyl silicate and 4-6 parts of ammonia water are added for stirring and reaction for 8-10 hours, and after the reaction is completed, washing and drying are performed to obtain a ferroferric oxide composite material; 3-5 parts of the ferroferric oxide composite material are added to 280-300 parts of deionized water for ultrasonic dispersion for 30-40 minutes, and then 1-3 parts of 3-aminopropyltriethoxysilane are added, the pH is adjusted to 7.4-7.6, and the reaction is stirred at 70-75° C. for 10-12 hours. After the reaction is completed, centrifugation, washing, and drying are performed to obtain a modified ferroferric oxide composite material; Step S2: by weight, 15 to 20 parts of chromium oxide, 15 to 20 parts of modified ferrosoferric oxide composite material, 5 to 10 parts of cobalt oxide and 5 to 10 parts of kaolin are mixed uniformly to obtain a pigment; Step S3: In parts by weight, 45 to 50 parts of epoxy resin, 8 to 10 parts of phenolic resin, 0.2 to 0.5 parts of dispersant and 0.2 to 0.5 parts of dimethyl silicone oil are added to 80 to 100 parts of solvent, stirred at 70 to 80° C. for 2 to 4 hours, then the temperature is controlled to 40 to 50° C., 40 to 60 parts of the pigment are added and stirred evenly to obtain a mixture, and the mixture is transferred to a horizontal sand mill and ground for 4 to 6 hours to obtain a thermal transfer ink.
[0007] The modified ferrosoferric oxide composite material contains a mesoporous silica carrier and surface amino groups, which can give the material good thixotropy, help the ink maintain good fluidity and printability during the printing process, and quickly form a stable surface layer after printing, reducing diffusion and sagging, and effectively improving the coloring power of the ink.
[0008] As a preferred solution, the kaolin is carboxylated kaolin; the preparation method of the carboxylated kaolin comprises: dispersing 20 to 30 parts of olefinated kaolin in 250 to 300 parts of ethyl acetate by weight, then adding 10 to 14 parts of itaconic acid and 1 to 3 parts of benzoyl peroxide, reacting at 80 to 90° C. for 4 to 6 hours, cooling to room temperature after the reaction, centrifuging, washing, and vacuum drying to obtain carboxylated kaolin.
[0009] As a preferred scheme, the preparation method of the olefinated kaolin comprises: adding 1 to 3 parts of sodium hydroxide to 250 to 300 parts of deionized water by weight, stirring and dissolving, then adding 20 to 30 parts of kaolin, stirring at 80 to 90° C. for 8 to 10 hours, centrifuging, washing, and drying to obtain activated kaolin; uniformly mixing 10 to 20 parts of deionized water and 80 to 90 parts of anhydrous ethanol, adding 20 to 30 parts of the activated kaolin, adjusting the pH to 5.2 to 5.4 with an acetic acid solution with a mass concentration of 10%, ultrasonically dispersing for 40 to 60 minutes, then adding 5 to 7 parts of γ-(methacryloyloxy)propyltrimethoxysilane, reacting at 85 to 90° C. for 6 to 8 hours, cooling to room temperature after the reaction, centrifuging, washing, and drying to obtain olefinated kaolin.
[0010] As a preferred solution, the particle size of the kaolin is 60-90 nm, and the specific surface area is 160-180 m 2 / g.
[0011] Carboxylated kaolin can affect the volatilization of solvents in inks, causing them to be released quickly on the surface while maintaining appropriate internal fluidity, thereby prompting the ink surface to dry quickly. By optimizing the volatilization rate of solvents through carboxylated kaolin, the initial drying properties of thermal transfer inks can be improved.
[0012] As a preferred solution, the epoxy resin is a bisphenol epoxy resin and a naphthalene epoxy resin; the mass ratio of the bisphenol epoxy resin to the naphthalene epoxy resin is (1-2):1.
[0013] As a preferred solution, the phenolic resin is a silicon-containing phenolic resin; the preparation method of the silicon-containing phenolic resin comprises: in parts by weight, 6 to 8 parts of oxalic acid and 4 to 6 parts of sulfuric acid are mixed evenly, then 100 to 110 parts of resorcinol are added and stirred evenly, 10 to 12 parts of formaldehyde are added at 90 to 95° C. and kept warm for 50 to 60 minutes; then 2 to 4 parts of sodium hydroxide and 4 to 6 parts of methyltrimethoxysilane are added at 100 to 110° C., the reaction is stirred for 1 to 3 hours, and the reaction is cooled to room temperature after completion to obtain the silicon-containing phenolic resin.
[0014] Silicone-containing phenolic resin improves interfacial compatibility by introducing siloxane groups, thereby being able to better wet the surface of the substrate, ensuring uniform spreading of the ink, and reducing the generation of bubbles and voids, which helps to increase the contact area between the ink and the substrate and enhance adhesion.
[0015] As a preferred solution, the dispersant is selected from any one of sodium hexametaphosphate, sodium tripolyphosphate, and sodium pyrophosphate, or a combination of at least two thereof.
[0016] As a preferred solution, the solvent is selected from any one of acetone, butanone, and cyclohexanone, or a combination of at least two of them.
[0017] The second aspect of the present invention provides a thermal transfer ink prepared by the preparation method described in the first aspect.
[0018] The third aspect of the present invention provides an application of the thermal transfer ink prepared by the preparation method described in the first aspect in the field of printing.
[0019] Compared with the prior art, the advantages and beneficial effects of the present invention are: 1. The modified ferrosoferric oxide composite material of the present invention is loaded on a mesoporous silica carrier and amino groups are introduced through surface treatment, while kaolin is introduced through modification treatment. The molecular chain segments of the silicon-containing phenolic resin have hydroxyl groups. The above active groups can be combined with the epoxy groups of the epoxy resin to form an interpenetrating network structure. The polymer can form a stronger interface bond with the surface of the substrate through chemical interaction, thereby improving the adhesion of the ink; at the same time, the high specific surface area of some materials ensures that the pigment is evenly distributed, thereby improving the tinting strength and initial drying properties.
[0020] 2. The modified ferrosoferric oxide composite material of the present invention contains a mesoporous silica carrier and a surface amino group, which can give the material good thixotropy, help the ink to maintain good fluidity and printability during the printing process, and quickly form a stable surface layer after printing, reduce diffusion and sagging, and effectively improve the coloring power of the ink.
[0021] 3. The carboxylated kaolin of the present invention can affect the volatilization of the solvent in the ink, causing it to be quickly released on the surface while maintaining appropriate internal fluidity, thereby prompting the ink surface to dry quickly. The carboxylated kaolin can optimize the volatilization rate of the solvent and improve the initial drying of the thermal transfer ink.
[0022] 4. The silicon-containing phenolic resin of the present invention improves the interfacial compatibility by introducing siloxane groups, thereby being able to better wet the surface of the substrate, ensuring uniform spreading of the ink, and reducing the generation of bubbles and voids, which helps to increase the contact area between the ink and the substrate and enhance the adhesion. DETAILED DESCRIPTION
[0023] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] The sources of some components in the embodiments and comparative examples are as follows: Chromium oxide, CAS No. 12182-82-0, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Commercially available ferrosoferric oxide, CAS No. 1317-61-9, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Cobalt oxide, CAS No. 1307-96-6, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Commercially available kaolin I, product number TG-Y-3, particle size 80nm, specific surface area 180m 2 / g, purchased from Guangzhou Changyu Chemical Co., Ltd.; Commercially available kaolin II, product number 1332-58-7, particle size 300nm, specific surface area 32m 2 / g, purchased from Shandong Zaozhuang Sanxing High-tech Materials Co., Ltd.; Bisphenol type epoxy resin, model jER828EL, purchased from Mitsubishi Chemical Corporation; Naphthalene epoxy resin, model ESN-475V, purchased from Nippon Steel Chemical Materials Co., Ltd.; Phenolic resin, model PF-8010, purchased from Shandong Shengquan New Materials Co., Ltd.; Sodium hexametaphosphate, CAS No. 10124-56-8, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Sodium tripolyphosphate, CAS No. 7758-29-4, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Sodium pyrophosphate, CAS No. 7722-88-5, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Dimethyl silicone oil, CAS No. 9016-00-6, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Tetraethyl silicate, CAS No. 78-10-4, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; 3-Aminopropyltriethoxysilane, CAS No. 919-30-2, was purchased from Sinopharm Chemical Reagent Co., Ltd.; γ-(Methacryloyloxy)propyltrimethoxysilane, CAS No. 2530-85-0, purchased from Sinopharm Chemical Reagent Co., Ltd.; Itaconic acid, CAS No. 97-65-4, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Benzoyl peroxide, CAS No. 94-36-0, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Resorcinol, CAS number 108-46-3, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Formaldehyde, CAS No. 50-00-0, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Methyltrimethoxysilane, CAS No. 1185-55-3, was purchased from Sinopharm Chemical Reagent Co., Ltd.
[0025] Example 1 This embodiment provides a method for preparing a thermal transfer ink, comprising the following steps: Preparation of carboxylated kaolin: (1) Add 3 parts of sodium hydroxide to 300 parts of deionized water and stir to dissolve, then add 30 parts of kaolin I (particle size 80 nm, specific surface area 180 m 2 / g), stirred at 90℃ for 8h, centrifuged, washed and dried to obtain activated kaolin; 20 parts of deionized water and 90 parts of anhydrous ethanol were mixed evenly, 30 parts of the activated kaolin were added, the pH was adjusted to 5.4 with 10% acetic acid solution, ultrasonically dispersed for 60min, and then 7 parts of γ-(methacryloyloxy)propyltrimethoxysilane were added, reacted at 90℃ for 6h, cooled to room temperature after the reaction, centrifuged, washed and dried to obtain olefinic kaolin. (2) In parts by weight, 30 parts of olefinic kaolin were dispersed in 300 parts of ethyl acetate, and then 14 parts of itaconic acid and 3 parts of benzoyl peroxide were added, reacted at 90℃ for 4h, cooled to room temperature after the reaction, centrifuged, washed and dried in vacuum to obtain carboxylated kaolin.
[0026] Preparation of silicon-containing phenolic resin: In parts by weight, 8 parts of oxalic acid and 6 parts of sulfuric acid are mixed evenly, then 110 parts of resorcinol are added and stirred evenly, 12 parts of formaldehyde are added at 95°C and kept warm for 50 minutes; then 4 parts of sodium hydroxide and 6 parts of methyltrimethoxysilane are added at 110°C, the reaction is stirred for 1 hour, and after the reaction is completed, the mixture is cooled to room temperature to obtain a silicon-containing phenolic resin.
[0027] Step S1: in parts by weight, 140 parts of anhydrous ethanol and 40 parts of deionized water are mixed evenly, and then 3 parts of ferrosoferric oxide are added for ultrasonic dispersion for 60 minutes, and then 10 parts of tetraethyl silicate and 6 parts of ammonia water are added for stirring and reaction for 10 hours. After the reaction is completed, the mixture is washed and dried to obtain a ferrosoferric oxide composite material; 5 parts of the ferrosoferric oxide composite material are added to 300 parts of deionized water for ultrasonic dispersion for 40 minutes, and then 3 parts of 3-aminopropyltriethoxysilane are added, the pH is adjusted to 7.6, and the mixture is stirred and reacted at 75° C. for 10 hours. After the reaction is completed, the mixture is centrifuged, washed, and dried to obtain a modified ferrosoferric oxide composite material; Step S2: by weight, 20 parts of chromium oxide, 20 parts of modified ferrosoferric oxide composite material, 10 parts of cobalt oxide and 10 parts of carboxylated kaolin are mixed evenly to obtain a pigment; Step S3: In parts by weight, 45 parts of epoxy resin (30 parts of bisphenol epoxy resin and 15 parts of naphthalene epoxy resin), 10 parts of silicon-containing phenolic resin, 0.5 parts of sodium hexametaphosphate and 0.5 parts of dimethyl silicone oil are added to 100 parts of acetone, stirred at 80°C for 2 hours, then the temperature is controlled to 50°C, 60 parts of the pigment are added and stirred evenly to obtain a mixture, and the mixture is transferred to a horizontal sand mill and ground for 6 hours to obtain a thermal transfer ink.
[0028] Example 2 This embodiment provides a method for preparing a thermal transfer ink, comprising the following steps: The preparation method of carboxylated kaolin comprises: (1) adding 1 part of sodium hydroxide to 250 parts of deionized water, stirring and dissolving, and then adding 20 parts of kaolin I (with a particle size of 80 nm and a specific surface area of 180 m 2 / g), stirred at 80℃ for 10h, centrifuged, washed and dried to obtain activated kaolin; 10 parts of deionized water and 80 parts of anhydrous ethanol were mixed evenly, 20 parts of the activated kaolin were added, the pH was adjusted to 5.2 with 10% acetic acid solution, ultrasonically dispersed for 40min, and then 5 parts of γ-(methacryloyloxy)propyltrimethoxysilane were added, reacted at 85℃ for 8h, cooled to room temperature after the reaction, centrifuged, washed and dried to obtain olefinic kaolin. (2) In parts by weight, 20 parts of olefinic kaolin were dispersed in 250 parts of ethyl acetate, and then 10 parts of itaconic acid and 1 part of benzoyl peroxide were added, reacted at 80℃ for 6h, cooled to room temperature after the reaction, centrifuged, washed and dried in vacuum to obtain carboxylated kaolin.
[0029] The preparation method of the silicon-containing phenolic resin comprises: mixing 6 parts of oxalic acid and 4 parts of sulfuric acid in parts by weight, then adding 100 parts of resorcinol and stirring evenly, adding 12 parts of formaldehyde at 90° C. and keeping warm for 60 minutes; then adding 2 parts of sodium hydroxide and 4 parts of methyltrimethoxysilane at 100° C., stirring and reacting for 3 hours, cooling to room temperature after the reaction is completed, and obtaining the silicon-containing phenolic resin.
[0030] Step S1: in parts by weight, 120 parts of anhydrous ethanol and 30 parts of deionized water are mixed evenly, then 1 part of ferroferric oxide is added and ultrasonically dispersed for 40 minutes, then 8 parts of tetraethyl silicate and 4 parts of ammonia water are added and stirred for reaction for 8 hours, and after the reaction is completed, the mixture is washed and dried to obtain a ferroferric oxide composite material; 3 parts of the ferroferric oxide composite material are added to 280 parts of deionized water and ultrasonically dispersed for 30 minutes, and then 1 part of 3-aminopropyltriethoxysilane is added, the pH is adjusted to 7.4, and the mixture is stirred for reaction at 70° C. for 12 hours, and after the reaction is completed, the mixture is centrifuged, washed, and dried to obtain a modified ferroferric oxide composite material; Step S2: by weight, 15 parts of chromium oxide, 15 parts of modified ferrosoferric oxide composite material, 5 parts of cobalt oxide and 5 parts of carboxylated kaolin are mixed evenly to obtain a pigment; Step S3: In parts by weight, 50 parts of epoxy resin (25 parts of bisphenol epoxy resin and 25 parts of naphthalene epoxy resin), 8 parts of silicon-containing phenolic resin, 0.2 parts of sodium tripolyphosphate and 0.2 parts of dimethyl silicone oil are added to 80-100 parts of butanone, stirred at 70°C for 4 hours, then the temperature is controlled to 40°C, 40 parts of the pigment are added and stirred evenly to obtain a mixture, and the mixture is transferred to a horizontal sand mill and ground for 4 hours to obtain a thermal transfer ink.
[0031] Example 3 This embodiment provides a method for preparing a thermal transfer ink, comprising the following steps: The preparation method of carboxylated kaolin comprises: (1) adding 2 parts of sodium hydroxide to 280 parts of deionized water by weight, stirring and dissolving, and then adding 25 parts of kaolin I (with a particle size of 80 nm and a specific surface area of 180 m 2 / g), stirred at 85℃ for 9h, centrifuged, washed and dried to obtain activated kaolin; 15 parts of deionized water and 85 parts of anhydrous ethanol were mixed evenly, 25 parts of the activated kaolin were added, the pH was adjusted to 5.3 with 10% acetic acid solution, ultrasonically dispersed for 50min, and then 6 parts of γ-(methacryloyloxy)propyltrimethoxysilane were added, reacted at 88℃ for 7h, cooled to room temperature after the reaction, centrifuged, washed and dried to obtain olefinic kaolin. (2) In parts by weight, 25 parts of olefinic kaolin were dispersed in 280 parts of ethyl acetate, and then 12 parts of itaconic acid and 2 parts of benzoyl peroxide were added, reacted at 85℃ for 5h, cooled to room temperature after the reaction, centrifuged, washed and dried in vacuum to obtain carboxylated kaolin.
[0032] The preparation method of the silicon-containing phenolic resin comprises: mixing 7 parts of oxalic acid and 4 to 6 parts of sulfuric acid by weight, then adding 105 parts of resorcinol and stirring evenly, adding 11 parts of formaldehyde at 92° C. and keeping warm for 55 minutes; then adding 3 parts of sodium hydroxide and 5 parts of methyltrimethoxysilane at 105° C., stirring and reacting for 2 hours, cooling to room temperature after the reaction is completed, and obtaining the silicon-containing phenolic resin.
[0033] Step S1: in parts by weight, 130 parts of anhydrous ethanol and 35 parts of deionized water are mixed evenly, then 2 parts of ferrosoferric oxide are added and ultrasonically dispersed for 50 minutes, and then 9 parts of tetraethyl silicate and 5 parts of ammonia water are added and stirred for reaction for 9 hours. After the reaction is completed, the mixture is washed and dried to obtain a ferrosoferric oxide composite material; 4 parts of the ferrosoferric oxide composite material are added to 290 parts of deionized water and ultrasonically dispersed for 35 minutes, and then 2 parts of 3-aminopropyltriethoxysilane are added, the pH is adjusted to 7.5, and the mixture is stirred for reaction at 72° C. for 11 hours. After the reaction is completed, the mixture is centrifuged, washed, and dried to obtain a modified ferrosoferric oxide composite material; Step S2: by weight, 18 parts of chromium oxide, 17 parts of modified ferrosoferric oxide composite material, 8 parts of cobalt oxide and 7 parts of carboxylated kaolin are mixed uniformly to obtain a pigment; Step S3: In parts by weight, 48 parts of epoxy resin (30 parts of bisphenol epoxy resin and 18 parts of naphthalene epoxy resin), 9 parts of silicon-containing phenolic resin, 0.4 parts of sodium pyrophosphate and 0.4 parts of dimethyl silicone oil are added to 90 parts of cyclohexanone, stirred at 75°C for 3 hours, then the temperature is controlled to 45°C, 50 parts of the pigment is added and stirred evenly to obtain a mixture, and the mixture is transferred to a horizontal sand mill and ground for 5 hours to obtain a thermal transfer ink.
[0034] Comparative Example 1 The difference between this comparative example and Example 1 is that commercially available ferrosoferric oxide is used to replace the modified ferrosoferric oxide composite material.
[0035] Comparative Example 2 The difference between this comparative example and Example 1 is that commercially available kaolin is used instead of carboxylated kaolin.
[0036] Comparative Example 3 The difference between this comparative example and Example 1 is that commercially available kaolin II is used to replace commercially available kaolin I in the preparation.
[0037] Comparative Example 4 The difference between this comparative example and Example 1 is that a commercially available phenolic resin is used instead of the silicon-containing phenolic resin.
[0038] Comparative Example 5 The difference between this comparative example and Example 1 is that the amount of bisphenol epoxy resin is changed to 35 parts, and the amount of naphthalene epoxy resin is changed to 10 parts.
[0039] Comparative Example 6 The difference between this comparative example and Example 1 is that the amount of bisphenol epoxy resin is changed to 15 parts, and the amount of naphthalene epoxy resin is changed to 30 parts.
[0040] Performance Testing The thermal transfer inks prepared in the above examples and comparative examples were subjected to the following tests: (1) Tinting strength test The tinting strength is tested in accordance with the requirements of GB / T 13217.1-2020 Test method for ink color and tinting strength.
[0041] (2) Initial drying test The initial drying property is tested according to the requirements of GB / T 13217.5-2023 Test method for ink drying.
[0042] (3) Adhesion fastness test The adhesion fastness is tested according to the requirements of GB / T 13217.7-2023 Test method for ink adhesion.
[0043] Table 1 Performance test results
[0044] It can be seen from the above performance test results that the thermal transfer ink of Examples 1-3 has the best comprehensive effect, with a tinting strength of 98.9~99.4%, an initial drying time of 32~34s, and an adhesion fastness of 93.1~93.7%. This is mainly because it uses a modified ferrosoferric oxide composite material and carboxylated kaolin, and is matched with other components to obtain a mixed filler. At the same time, a silicon-containing phenolic resin is introduced into the polymer system, which effectively improves the tinting strength and adhesion fastness of the ink and ensures good initial drying.
[0045] The comparative examples did not adopt the necessary technical solutions, resulting in that the corresponding performance tests were significantly worse than those of the embodiments. Compared with Example 1, the comparative example 1 used commercially available ferroferric oxide to replace the modified ferroferric oxide composite material, and the tinting power decreased, the initial drying property became worse, and the adhesion fastness decreased; compared with Example 1, the comparative example 2 used commercially available kaolin to replace the carboxylated kaolin, and the tinting power decreased, the initial drying property became worse, and the adhesion fastness decreased; compared with Example 1, the comparative example 3 used commercially available kaolin II to replace the commercially available kaolin I, and the particle size of the commercially available kaolin II was too large and the specific surface area was too small, resulting in poor modification effect, and the tinting power decreased, the initial drying property became worse, and the adhesion fastness decreased. Low; Compared with Example 1, Comparative Example 4 uses commercially available phenolic resin to replace silicon-containing phenolic resin, resulting in decreased tinting power, poor initial drying, and reduced adhesion; Compared with Example 1, Comparative Example 5 changes the amount of bisphenol epoxy resin to 35 parts and the amount of naphthalene epoxy resin to 10 parts. Due to the excessive amount of bisphenol epoxy resin, the compounding effect is not good, resulting in decreased tinting power, poor initial drying, and reduced adhesion; Compared with Example 1, Comparative Example 6 changes the amount of bisphenol epoxy resin to 15 parts and the amount of naphthalene epoxy resin to 30 parts. Due to the excessive amount of naphthalene epoxy resin, the compounding effect is not good, resulting in decreased tinting power, poor initial drying, and reduced adhesion. The above experimental results further prove the importance of the technical solution defined in the present invention for its technical effect.
[0046] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a thermal transfer ink, characterized in that: The following steps are involved: Step S1: in parts by weight, 120-140 parts of anhydrous ethanol and 30-40 parts of deionized water are mixed evenly, and then 1-3 parts of ferroferric oxide are added for ultrasonic dispersion for 40-60 minutes, and then 8-10 parts of tetraethyl silicate and 4-6 parts of ammonia water are added for stirring and reaction for 8-10 hours, and after the reaction is completed, washing and drying are performed to obtain a ferroferric oxide composite material; 3-5 parts of the ferroferric oxide composite material are added to 280-300 parts of deionized water for ultrasonic dispersion for 30-40 minutes, and then 1-3 parts of 3-aminopropyltriethoxysilane are added, the pH is adjusted to 7.4-7.6, and the reaction is stirred at 70-75° C. for 10-12 hours. After the reaction is completed, centrifugation, washing, and drying are performed to obtain a modified ferroferric oxide composite material; Step S2: by weight, 15 to 20 parts of chromium oxide, 15 to 20 parts of modified ferrosoferric oxide composite material, 5 to 10 parts of cobalt oxide and 5 to 10 parts of kaolin are mixed uniformly to obtain a pigment; Step S3: In parts by weight, 45 to 50 parts of epoxy resin, 8 to 10 parts of phenolic resin, 0.2 to 0.5 parts of dispersant and 0.2 to 0.5 parts of dimethyl silicone oil are added to 80 to 100 parts of solvent, stirred at 70 to 80° C. for 2 to 4 hours, then the temperature is controlled to 40 to 50° C., 40 to 60 parts of the pigment are added and stirred evenly to obtain a mixture, and the mixture is transferred to a horizontal sand mill and ground for 4 to 6 hours to obtain a thermal transfer ink.
2. The method for preparing a thermal transfer ink according to claim 1, characterized in that: The kaolin is carboxylated kaolin; The preparation method of the carboxylated kaolin comprises: dispersing 20 to 30 parts of olefinated kaolin in 250 to 300 parts of ethyl acetate by weight, then adding 10 to 14 parts of itaconic acid and 1 to 3 parts of benzoyl peroxide, reacting at 80 to 90° C. for 4 to 6 hours, cooling to room temperature after the reaction, centrifuging, washing, and vacuum drying to obtain the carboxylated kaolin.
3. The method for preparing a thermal transfer ink according to claim 2, characterized in that: The preparation method of the alkenylated kaolin comprises: adding 1 to 3 parts of sodium hydroxide to 250 to 300 parts of deionized water by weight, stirring and dissolving, then adding 20 to 30 parts of kaolin, stirring at 80 to 90° C. for 8 to 10 hours, centrifuging, washing, and drying to obtain activated kaolin; uniformly mixing 10 to 20 parts of deionized water and 80 to 90 parts of anhydrous ethanol, adding 20 to 30 parts of the activated kaolin, adjusting the pH to 5.2 to 5.4 with an acetic acid solution with a mass concentration of 10%, ultrasonically dispersing for 40 to 60 minutes, then adding 5 to 7 parts of γ-(methacryloyloxy)propyltrimethoxysilane, reacting at 85 to 90° C. for 6 to 8 hours, cooling to room temperature after the reaction, centrifuging, washing, and drying to obtain the alkenylated kaolin.
4. The method for preparing a thermal transfer ink according to claim 3, characterized in that: The particle size of the kaolin is 60-90 nm, and the specific surface area is 160-180 m 2 / g.
5. The method for preparing a thermal transfer ink according to claim 1, characterized in that: The epoxy resin is a bisphenol epoxy resin and a naphthalene epoxy resin; the mass ratio of the bisphenol epoxy resin to the naphthalene epoxy resin is (1-2):
1.
6. The method for preparing a thermal transfer ink according to claim 1, characterized in that: The phenolic resin is a silicon-containing phenolic resin; The preparation method of the silicon-containing phenolic resin comprises: mixing 6-8 parts of oxalic acid and 4-6 parts of sulfuric acid by weight, then adding 100-110 parts of resorcinol and stirring evenly, adding 10-12 parts of formaldehyde at 90-95° C. and keeping warm for 50-60 minutes; then adding 2-4 parts of sodium hydroxide and 4-6 parts of methyltrimethoxysilane at 100-110° C., stirring for reaction for 1-3 hours, and cooling to room temperature after the reaction is completed to obtain the silicon-containing phenolic resin.
7. The method for preparing a thermal transfer ink according to claim 1, characterized in that: The dispersant is selected from any one of sodium hexametaphosphate, sodium tripolyphosphate, and sodium pyrophosphate, or a combination of at least two thereof.
8. The method for preparing a thermal transfer ink according to claim 1, characterized in that: The solvent is selected from any one of acetone, butanone, and cyclohexanone, or a combination of at least two thereof.
9. A thermal transfer ink, characterized in that: Prepared according to the method according to any one of claims 1 to 8.
10. Use of the thermal transfer ink prepared by the method according to any one of claims 1 to 8 in the field of printing.
Citation Information
Patent Citations
Heat transfer printing ink as well as preparation method and application thereof
CN117924995A
Method for removing viruses and diseased cells in blood
CN110227195A
Anti-seepage and anti-crack concrete admixture and preparation method thereof
CN116675460A
Preparation method of silane and epoxy resin modified phenolic resin adhesive
CN118652650A
High-flame-retardant strong-heat-insulation composite material for fire mask and preparation method thereof
CN118703002A